Atratividade para adultos e preferência para oviposição de Bemisia tabaci (Genn.) biótipo B (Hemiptera: Aleyrodidae) em genótipos de Cucurbita spp - Costa Zache, Ronelza Rodrigues da; Lopes Baldin, Edson Luiz [UNESP]; Zache, Bruno [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The objective was to evaluate the oviposition preference and attractiveness of squash genotypes (Cucurbita spp.) to Bemisia tabaci biotype B. For bioassays, B. tabaci rearing biotype B was kept under greenhouse conditions. Twenty genotypes of Cucurbita spp. ('Alicia AF 9354', 'Aline AF 9353', 'Golden Delight', 'Nova Caravela', 'Menina Morena', 'Novita', 'AF-6741', 'Atlas', 'Barbara 305', 'Menina Brasileira', 'Caserta', 'Itapua 301', 'Tamara', 'Samira', 'Canhao Seca Gigante', 'Exposicao', 'Novita Plus', 'Daiane', 'Formosa', 'Sandy') were evaluated in trials (attractiveness and oviposition choice), under laboratory and greenhouse. The attractiveness (adults/cm(2)) was assessed et 12, 24, 48 and 72 hours after release. After 72 hours leaves were collected for counting the number of eggs (free choice). The area of the sheets were measured to obtain the number of eggs/cm(2) number of adults and / cm(2). The attractiveness index s (AI) and oviposition preference index (OPI) were calculated, and the genotype 'Novita' was adopted as the standard susceptible. The genotype 'Golden Delight' was the most attractive to adults of B. tabaci biotype B. 'Sandy' 'Daiane' and 'Formosa' showed low attractiveness and 'Golden Delight' was the most atractive to B. tabaci biotype B adults. 'Sandy', 'Exposicao', 'Daiane', 'Atlas', 'Tamara' and 'Formosa' expressed no preference for free choise assay. According to the attractiveness index (AI) the genotype 'Golden Delight' was the most attractive to adults of B. tabaci biotype B, and between repellents stood out 'Sandy', 'Daiane', 'Formosa', 'Novita Plus', 'Atlas', 'Barbara 305', 'Canhao Seca Gigante' and 'Menina Brasileira'. The genotypes 'Nova Caravela', 'Golden Delight', 'Aline AF 9353' and 'Samira' are considered by stimulating oviposition preference index (OPI), while the genotypes 'Sandy', 'Exposicao', 'Daiane', 'Atlas', 'Tamara', 'Formosa', 'Menina Morena' and 'Itapua 301' were considered deterrents.
Adult attractiveness and non-preference for oviposition of Bemisia tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) in genotypes of Cucurbita spp
Keywords: Resistance of plants; whitefly; squash; Cucurbitaceae